Análise do desenvolvimento da síndrome de Burnout em treinadores de voleibol da superliga masculina 2010/2011 - Marisa Lúcia de Mello Santiago (2012)
The objective of this study was to analyze the development of burnout syndrome in high performance volleyball coaches. It was aimed at identifying which activities undertaken by coaches generate stress resulting from their work, possibly leading to chronic stress, and even, burnout syndrome. A qualitative methodology, founded on the dialectic approach focused on the socio-historical perspective was adopted. During the data collection, fifteen interviews were conducted with all of the coaches participating in the 2010/2011 Mens Volleyball Super League. The data were submitted to content analysis. As a result, themes were revealed, allowing for the recognition of three empirical categories: Factors that May Cause Burnout Syndrome, The Manifestations of Burnout, and, The Effects of Stress/Burnout. The results indicate that coaches have various factors that generate stress in their profession. These factors are found in various professions, and in the specific labor process of competitive volleyball. In their practice, these professionals guide themselves by the theoretical foundations of the modality and by the need to meet the demands of their team, often taking on an excessive load of responsibilities, obstacles to be overcome, and goals to achieve. It was concluded that the coaches live with the challenge of balancing technical and tactical measures with the management of other functions, leading to an overload of tasks, short recovery time, and difficulty in enduring stressful situations, a challenge which can lead to the development of Burnout syndrome.